2018
DOI: 10.1093/mnras/sty467
|View full text |Cite
|
Sign up to set email alerts
|

Alone on a wide wide sea. The origin of SECCO 1, an isolated star-forming gas cloud in the Virgo cluster*†‡

Abstract: SECCO 1 is an extremely dark, low-mass (M 10 5 M ), star-forming stellar system lying in the Low Velocity Cloud (LVC) substructure of the Virgo cluster of galaxies, and hosting several Hii regions. Here we review our knowledge of this remarkable system, and present the results of (a) additional analysis of our panoramic spectroscopic observations with MUSE, (b) the combined analysis of Hubble Space Telescope and MUSE data, and (c) new narrow-band observations obtained with OSIRIS@GTC to search for additional H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 97 publications
3
27
0
Order By: Relevance
“…However, de los Reyes & Kennicutt (2019) have recently shown that in local dwarf galaxies the Schmidt law for star formation (Schmidt 1959) does not seem to exhibit any threshold, as even the lowest surface brightness regions show the presence of very young stars. An even more extreme confirmation of this is represented by an utterly low density (n ∼ 0.01 cm −3 ) -yet, star-forming -galaxy recently found in the Virgo cluster (Bellazzini et al 2018). All in all, since UFDs are thought to represent the extreme limit of the galaxy formation process (Simon 2019), the assumed gas and star distributions for our model Boötes I galaxy may well be not quite so unreasonable.…”
Section: Numerical Set-upsupporting
confidence: 54%
“…However, de los Reyes & Kennicutt (2019) have recently shown that in local dwarf galaxies the Schmidt law for star formation (Schmidt 1959) does not seem to exhibit any threshold, as even the lowest surface brightness regions show the presence of very young stars. An even more extreme confirmation of this is represented by an utterly low density (n ∼ 0.01 cm −3 ) -yet, star-forming -galaxy recently found in the Virgo cluster (Bellazzini et al 2018). All in all, since UFDs are thought to represent the extreme limit of the galaxy formation process (Simon 2019), the assumed gas and star distributions for our model Boötes I galaxy may well be not quite so unreasonable.…”
Section: Numerical Set-upsupporting
confidence: 54%
“…SECCO 1 is a faint, star-forming stellar system with some diffuse Hα emission. Its physical size, ∼ 1.2 kpc in radius for each of the two pieces (Bellazzini et al 2018), is much smaller than the OC discussed in this paper. It has a rather high metallicity of ∼ half solar for its low optical luminosity (Beccari et al 2017;Sand et al 2017).…”
Section: Origin Of the Ocmentioning
confidence: 61%
“…none found in the Hα surveys in the Coma cluster, A851, and CL0024+17 (Yagi et al 2010(Yagi et al , 2015. The only other isolated Hα cloud in a galaxy cluster we are aware of is SECCO 1 in the Virgo cluster (Beccari et al 2017;Sand et al 2017;Bellazzini et al 2018). SECCO 1 is a faint, star-forming stellar system with some diffuse Hα emission.…”
Section: Origin Of the Ocmentioning
confidence: 89%
“…In particular aE is nearly filamentary, with a shell morphology that is observed If PW 1 is indeed the product of a small recent episode of star formation that occurred within a cold gas cloud, associated or not associated with the MS (see below) and likely triggered by interaction with Galactic gas, an interesing similarity, albeit at a smaller scale, can be noted with SECCO 1 (see Bellazzini et al 2018, and references therein). This is a low mass (M * = 10 5 M ) star-forming system (with no detection of stars older than ∼ 50 Myr) located in the outskirts of the Virgo cluster of galaxies, that is the possible prototype of a new class of stellar systems that are born in isolated H i clouds kept together by the external pressure of the surrounding hot gas (Sand 2017;Bellazzini et al 2018). SECCO 1 is fragmented in two pieces, each one with size of a few hundreds of pc, and will probably fragment into smaller pieces in the near future.…”
Section: Discussionmentioning
confidence: 99%